Tenure security and demand for land tenure regularization in Nigeria: Empirical evidence from Ondo and Kano states - Ghebru, Hosaena; Edeh, Hyacinth O.; Ali, Daniel; Deininger, Klaus; Okumo, Austen; Woldeyohannes, Sileshi (International Food Policy Research Institute, 2014)
The objectives of the research described in this report are to: provide general field information on physical, social, and institutional conditions in the pilot areas Kano and Ondo states that can be used to assess existing land tenure policy in Nigeria; assess the differentiated effect of existing land laws and practices on men and women in terms of access to, control over, and distribution of land by collecting gender-disaggregated data; contribute to better understanding of the magnitude, scope, and severity of tenure insecurity in the context of existing land laws and land policies; assess the efficiency of land-administration related service delivery by the public sector (e.g., dispute resolu-tion mechanisms).